Why public health might address the emerging role of vaccinomics? (Italian Journal of Public Health, 2010)
The greatest public health benefit of the advances brought about by the understanding of the human genome, completely sequenced in 2000, will likely occur as genomic medicine expands its focus from rare genetic disorders towards the inclusion of more common diseases also, such as coronary heart disease, diabetes mellitus, cancer and infectious disease. Advances in Genomics hold the promise of improving the delivery of health care, particularly that of preventive medicine, and of tailoring drug treatment.